2020
DOI: 10.3389/fimmu.2020.582939
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Organ Transplantation

Abstract: Current immunosuppressive therapy has led to excellent short-term survival rates in organ transplantation. However, long-term graft survival rates are suboptimal, and a vast number of allografts are gradually lost in the clinic. An increasing number of animal and clinical studies have demonstrated that monocytes and macrophages play a pivotal role in graft rejection, as these mononuclear phagocytic cells recognize alloantigens and trigger an inflammatory cascade that activate the adaptive immune response. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 180 publications
(193 reference statements)
0
48
2
Order By: Relevance
“…However, if the original injury persists, the inflammatory M1 phenotype causes progressive tissue damage (41). To corroborate this in vitro evidence, in vivo studies have indicated that allograft transplantation without immune suppression is associated with persistent M1-type BMM, while macrophages rapidly convert to M2-phenotype with adequate immune suppression (26,46,56). In summary, we hypothesize that surgical trauma causes proliferation of destructive M1 microglia that contribute to acute rejection, and dysregulation of the M1 phenotype leads to macrophage infiltrate surrounding chronically rejected RPE grafts.…”
Section: Section I: Transplant Immunologymentioning
confidence: 98%
See 3 more Smart Citations
“…However, if the original injury persists, the inflammatory M1 phenotype causes progressive tissue damage (41). To corroborate this in vitro evidence, in vivo studies have indicated that allograft transplantation without immune suppression is associated with persistent M1-type BMM, while macrophages rapidly convert to M2-phenotype with adequate immune suppression (26,46,56). In summary, we hypothesize that surgical trauma causes proliferation of destructive M1 microglia that contribute to acute rejection, and dysregulation of the M1 phenotype leads to macrophage infiltrate surrounding chronically rejected RPE grafts.…”
Section: Section I: Transplant Immunologymentioning
confidence: 98%
“…Early work in solid organ transplants demonstrated that Tcells are necessary and sufficient for allograft rejection (24)(25)(26). Subsequently, immunosuppressive regimen were developed that target T-cell activation at three steps: signal 1) binding by APCs, signal 2) costimulatory molecules and ligands, or signal 3) the trigger for cell proliferation (27).…”
Section: Section I: Transplant Immunologymentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibiting infiltration or activation of monocytes/macrophages by mycophenolate mofetil (MMF) seems to be a promising therapeutic strategy ( 74 ). Indeed, depletion of monocytes/macrophages attenuate neutrophils-related tissue damage at the early stage of transplant ( 75 77 ), while it may also prevent tissue repair and induction of tolerance at late stage due to loss of reprogrammed macrophages that participate in reconstitution of homeostasis ( 17 , 78 ). Moreover, chronic rejection mediated by M2-like macrophages is also an ineligible issue.…”
Section: Conclusion and Future Remarkmentioning
confidence: 99%